1999
DOI: 10.1148/radiology.211.2.r99ma36373
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pseudotumor of the Liver in Patients with Recurrent Pyogenic Cholangitis: CT-Histopathologic Correlation

Abstract: Although CT features are not specific, inflammatory pseudotumor should be included in the differential diagnosis in patients with recurrent pyogenic cholangitis and a hepatic mass detected at CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 27 publications
5
69
0
Order By: Relevance
“…However, only a few reports describe the radiologic findings of cholangiocarcinoma occurring in patients with hepatolithiasis [17][18][19]. In patients with hepatolithiasis, fibrotic masses in the bile duct walls and periductal hepatic parenchyma are often seen as a form of periductal tumorlike lesions and may appear similar to cholangiocarcinoma on CT [19]. Furthermore, in patients with hepatolithiasis, the stricture or stenosis caused by cholangiocarcinoma may not be easy to differentiate from that caused by stones [6,10,20].…”
mentioning
confidence: 99%
“…However, only a few reports describe the radiologic findings of cholangiocarcinoma occurring in patients with hepatolithiasis [17][18][19]. In patients with hepatolithiasis, fibrotic masses in the bile duct walls and periductal hepatic parenchyma are often seen as a form of periductal tumorlike lesions and may appear similar to cholangiocarcinoma on CT [19]. Furthermore, in patients with hepatolithiasis, the stricture or stenosis caused by cholangiocarcinoma may not be easy to differentiate from that caused by stones [6,10,20].…”
mentioning
confidence: 99%
“…Many mechanisms and hypothesized etiologic factors like infections, trauma, autoimmunity reactions, radiotherapy, and local reaction to changes in the walls of bile ducts are suggested [1][2][3][4][5][6][7]10,13,[18][19][20][21][22][23][24][25][26]. Some microorganisms that access the portal vein including Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Gram-positive cocci and Actinomyces were regarded as causative agents.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections (Epstein-Barr virus [20], hepatitis B and C virus) [10,27] and parasitic infestations (Schistosoma mansoni) may play role in the pathogenesis [18]. Some authors suggested that disturbance of biliary drainage, e.g., due to biliary stones [1,7], recurrent pyogenic cholangitis [4,26] or sclerosing cholangitis is also important [25]. The tumor was also noted in HIV infected persons [24].…”
Section: Discussionmentioning
confidence: 99%
“…Spots of more hypodense areas could not be found in the lesion. Simultaneously, the surrounding hepatic parenchyma may present small wedge shape or patchy of enhancing zone during the hepatic arterial phase [12] , which is caused by the inflammatory hyperemia involving the tissue near the inflammtory lesion. In contrast, SHCC lacks this feature.…”
Section: Hepatic Inflammatory Pseudotumormentioning
confidence: 99%